Constraining and enabling factors to using long-term climate information in decision-making. (4th July 2017) - Jones, Lindsey; Champalle, Clara; Chesterman, Sabrina; Cramer, Laura; Crane, Todd A.
Abstract : We carry out a structured review of the peer-reviewed literature to assess the factors that constrain and enable the uptake of long-term climate information in a wide range of sectoral investment and planning decisions. Common applications of long-term climate information are shown to relate to urban planning and infrastructure, as well as flood and coastal management. Analysis of the identified literature highlights five categories of constraints: disconnection between users and producers of climate information, limitations of climate information, financial and technical constraints, political economy and institutional constraints and finally psycho-social constraints. Five categories of enablers to the uptake of long-term climate information in decision-making are also identified: collaboration and bridge work, increased accessibility of climate information, improvement in the underlying science, institutional reform and windows of opportunity for building trust. Policy relevance Our review suggests that stand-alone interventions aimed at promoting the uptake of climate information into decision-making are unlikely to succeed without genuine and sustained relationships between producers and users. We also highlight that not every decision requires consideration of long-term climate information for successful outcomes to be achieved. This is particularly the case in the context of developing countries, where the immediacy of development challenges means that decision makers often prioritize short-term interventions. Care should therefore be taken to ensure that information is targeted towards investments and planning decisions that are relevant to longer-term timescales.